Z badań nad homeryzmami "Potopu" Henryka Sienkiewicza - Macjon, Józef (Collectanea Philologica, 1995)
In reference to a comparative study of Sienkiewicz' s historical trilogy three episodes in TheDeluge bear striking resemblance to those in Odyssey (translated by Lucjan Siemieński) - the factthat seems to have escaped to critics' notice. The story of Kmicic's bow, especially a description of the archer's action just about to shootan arrow, together with an accompanying simile (The Deluge, vol. 3, chap. XII) is patterned ona motif of Odysseus' bow (Odyssey, XXI, 11-33; 409-411).The episode in which Kuklinowski takes revenge on Kmicic, and then that of Kmicic'srevenge on Kuklinowski (The Deluge vol. 3, chap. XVIll) shows the writer's familiarity with thescene of Melanthios - the Goatherd's capture (Odyssey, XXII, 173-205).In the chase after Babinicz, The General Douglas comes across a bunch of Swedish soldiershanged by some Polish peasants (The Deluge, vol. 6, chap. IX). The story of the event is anexcelent example of the use of Homeric simile (Odyssey, XXII, 481--487).